A Heart of Wisdom - Puffer, Keith A. (2017)
Twenty-nine years ago, a medical trauma kindled the beginning of a spiritual transformation. The ordeal started with a late-night phone call that was followed by several stress-filled, disheartening events over ten days. In short, my father's unexpected death from an undetected arterial complication became a prompt from God to number the days of my life and gain a heart of wisdom (Psalm 90:12). Description of Dad's final days and his life-threatening medical condition, a ruptured abdominal aortic aneurysm, are presented. Moreover, interpretative commentary on Israel's lament in Psalm 90, particularly verse twelve, and personal applications of the transformative effects of the prayer and my father's passing are discussed.
Keywords: Bible. Psalms; HEART disease complications; PRAYER in Christianity; Spiritualism; Wisdom -- Religious aspects -- Christianity